Virulence studies of Indian populations of sorghum cyst nematode, Heterodera sorghi in maize - ., Rajkumar; Kaushal, K K (Indian Journal of Plant Protection, 2020)
Five sorghum cyst nematode, Heterodera sorghi populations, that cause nematode disease in maize, were collected from Kulu, Chamba (Himachal Pradesh), Tihri (Uttarakhand), Ghaziabad (Uttar Pradesh) and Kud (Jammu and Kashmir) to determine the degree/pattern of virulence in a collection of five populations against maize. Maize plants were inoculated with juveniles and assessed for the nematode multiplication and reduction in growth parameters. The results showed that decrease in shoot lengths was found to be non significant. However, significant reduction in fresh shoot and root weight was observed in maize due to all five populations at the initial inoculation level of 4 and 6 second stage juveniles (J2)/g soil compared to uninoculated control and which were significantly different from each other. Significant reduction in dry shoot and root weight of maize was recorded at the initial inoculum level of 2, 4 and 6 J2/g soil in all five populations except Ghaziabad population, where significant reduction of dry root weight was observed at initial inoculation level of 4 and 6 J2/g soil compared to uninoculated control. Maximum multiplication of the nematode was recorded at the highest level of nematode inoculum (6 J2/g of soil) and minimum at the lowest level (2 J2/g of soil). The Ghaziabad population was found to be more virulent among the five populations on maize and may be helpful in developing region oriented management strategy.